Integrating an Understanding of Islamic Economics into Service Quality and the Sustainability of Halal Tourism - Sulistiara Putri; Nur Fitri Hidayanti; Sahman Z; Ali Dalha Haruna (Fakultas Ekonomi, Universitas Semarang, 2026)
This study aims to examine the effect of Islamic economic understanding on service quality and the sustainability of halal tourism in West Nusa Tenggara Province. This research employs a quantitative approach using linear regression analysis with a sample of 108 respondents consisting of halal tourism service providers and users. The study proposes three hypotheses: (H1) An understanding of Islamic economics is predicted to have a positive and significant impact on the quality of halal tourism services; (H2) Service quality is assumed to have a positive and significant impact on the sustainability of halal tourism; and (H3) This study examines whether an understanding of Islamic economics directly contributes positively and significantly to the long-term sustainability of halal tourism. The results indicate that Islamic economic understanding has a positive and significant effect on both service quality and halal tourism sustainability. The regression analysis shows that the independent variable significantly contributes to the model, with a coefficient of 0.488 (t = 5.813, p < 0.001) for service quality and 0.427 (t = 6.132, p < 0.001) for sustainability. The model explains 24.2% of the variance in service quality and 26.2% in halal tourism sustainability, indicating moderate explanatory power. These findings suggest that a higher level of Islamic economic understanding among tourism stakeholders leads to improved service quality and strengthens the sustainability of halal tourism destinations. Therefore, this study recommends enhancing Islamic economic literacy and implementing structured training programs for industry players to ensure the consistent application of Sharia principles in service practices and destination management.